The relationship between oxidative balance score and circadian syndrome: evidence from the NHANES 2005-2018 - Xie, Lin; Li, Juan; Xu, Mingzhi; Lei, Yahan; Chen, Xushan; Xie, Jiajia (Frontiers in Endocrinology, 2024)
The oxidative balance score (OBS) is a composite indicator that evaluates the balance between prooxidants and antioxidants in one's diet and lifestyle. However, the relationship between OBS and circadian syndrome (CircS) has remained unexplored. This investigation aimed to determine a correlation between OBS and CircS.This population-based study examined 7,202 participants from the 2005 to 2018 National Health and Nutrition Examination Survey (NHANES), 1,433 of whom had CircS. We utilized weighted multivariate logistic regression, trend tests, subgroup analysis, and interaction tests to evaluate the correlation between OBS (total OBS, dietary OBS, and lifestyle OBS) and CircS. Restricted cubic splines (RCS) models and threshold effect analysis were used to explore nonlinear relationships.Multivariate logistic regression analysis indicated that the protective factor for CircS was a high OBS level (total OBS: Odds ratio (OR) = 0.95, 95% Confidence interval (CI): 0.93-0.97; dietary OBS: OR = 0.98, 95% CI: 0.96-1.00; lifestyle OBS: OR = 0.65, 95% CI: 0.61-0.69). Compared to the quartile 1 group, OBS (total OBS, dietary OBS, and lifestyle OBS) was negatively and statistically significantly associated with the risk of developing Circs in the quartile 4 group (total OBS: OR = 0.47, 95% CI: 0.32-0.70; dietary OBS: OR = 0.69, 95% CI: 0.48-0.99; lifestyle OBS: OR = 0.07, 95% CI: 0.04-0.11).According to subgroup analysis and interaction tests, there was an interaction effect between the association of lifestyle OBS and CircS in terms of education level (p for interaction = 0.01). Furthermore, we observed a nonlinear negative relationship between lifestyle OBS and CircS prevalence, with inflection points at 6 (p for nonlinearity = 0.002).The results showed a substantial negative connection between OBS and CircS. Encouraging foods filled with antioxidants and antioxidant-rich lifestyles may reduce the risk of CircS.